STANDAR PENGELOLAAN PENDIDIKAN INTEGRAL BERBASIS TAUHID DI PAUD AS SA’AADAH PALANGKA RAYA - Ummu Hany; Siminto Siminto (CV. ADIBA ASIHA AMIRA, 2022)
The problem discussed in this study is how the management standards of integrated monotheism-based education in PAUD As Sa'aadah Palangka Raya. This research is motivated by the existence of Management in As-Sa'aada PAUD which implements Tauhid-Based Integral Education Management Standards. This study aims to find out more deeply about the standard of monotheistic-based integral education management. In particular, this study aims to describe the planning, organizing, implementing and evaluating standards of monotheism-based integral education management at the As-Sa'aadah PAUD institution. This research uses a descriptive method with a qualitative approach, while the research subjects include: administrators and educators. Data collection techniques used are interviews, observation, and documentation. The results of the study can be described as education management standards carried out at As-Sa'aadah PAUD related to Tauhid-Based Integral Education. This study was conducted through several scientific approaches, especially the education management approach. This is because the main focus in this research is to carry out a real implementation in the management of monotheism-based integral education at As Sa'aadah Early Childhood Education. The results of this study indicate that the standard of management of Integral Education Based on Tauhid in PAUD As Sa'aadah Palangka Raya is well implemented. Planning, organizing, implementing and supervising or evaluating which involves all elements of the school including the principal, teachers, students and guardians of students can run as expected. Although in some cases there are things that are less than optimal. In the discussion of management standards discussed in this paper are related to the Management Standards of integral education based on monotheism. Where there are geographical differences, human resources, and different histories, and there are major influences from the Western paradigm. Thus, standardization is very important and needed considering the increasing number of PAUD. Until the management of PAUD is increasingly developed and the management is more supervised. Especially in the management of Integral Early Childhood Education Based on Tauhid which is carried out at As Sa'aadah Palangka Raya PAUD (BPM- PAUD Muslimat Hidayatullah, 2022). It is hoped that this paper can be used as study material for further discussions regarding management standards for Integral Early Childhood Education Based on Tauhid.